The relationship between maternal vitamin D levels and osteopenia development in preterm infants: A cross-sectional study - Razieh Sadat Tabatabaei; Seyed Reza Mirjalili; Atefeh Ashrafi; Farimah Shamsi (International Journal of Reproductive BioMedicine)
Background: Osteopenia of prematurity (OP) is characterized by reduced bone mineral content, and vitamin D deficiency may worsen OP by affecting bone metabolism.